International Experiences To Increase Employability for Education Doctoral Students. A Comparative Study. Issue 163 (3rd September 2019) - Davis, Brittany; Fedeli, Monica; Coryell, Joellen E.
Abstract: The authors examine current literature and practice focusing on employability of doctoral students, discuss a case study involving Italian and U.S. students presenting research at an international graduate student research conference, and discuss how that experience may impact student learning, development, and employability after completing their doctoral degrees.